2023
DOI: 10.1088/2515-7639/acada1
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials of human source for 3D printing strategies

Abstract: Three-dimensional printing has risen in recent years as a promising approach that fast-tracked the biofabrication of tissue engineering constructs that most resemble utopian tissue/organ replacements for precision medicine. Additionally, by using human-sourced biomaterials engineered towards optimal rheological proprieties of extrudable inks, the best possible scaffolds can be created. These can encompass native structure and function with a low risk of rejection, enhancing overall clinical outcomes; and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 262 publications
(283 reference statements)
0
6
0
Order By: Relevance
“…Within this framework, 3D printing, an additive manufacturing technology consisting of the LbL fabrication of 3D scaffolds with tunable sizes and geometries, programmed by means of computer-aided drafting (CAD), plays a relevant role as a promising tool for the replacement of damaged tissues. Differently from the off-of-shelf scaffold production or the common hydrogels scaffolds, 3D printing may allow the fabrication of novel 3D bioengineered tissue with promising properties [ 294 , 295 ].…”
Section: Chitosan-based Inks For 3d Printing Applicationsmentioning
confidence: 99%
“…Within this framework, 3D printing, an additive manufacturing technology consisting of the LbL fabrication of 3D scaffolds with tunable sizes and geometries, programmed by means of computer-aided drafting (CAD), plays a relevant role as a promising tool for the replacement of damaged tissues. Differently from the off-of-shelf scaffold production or the common hydrogels scaffolds, 3D printing may allow the fabrication of novel 3D bioengineered tissue with promising properties [ 294 , 295 ].…”
Section: Chitosan-based Inks For 3d Printing Applicationsmentioning
confidence: 99%
“…This entails mimicking the geometric requirements observed at the tissue level. 3D bioprinting offers unique opportunities in this context as recently outlined in several reviews, [42][43][44] in particular when considering the fabrication of more complex 3D bioprinted tissues both with regards to geometry and use of different cell types. However, although artificial cells only have been 3D printed, as reviewed elsewhere, [45,46] the potential of introducing artificial cells in tissue engineering scaffolds was recently highlighted by Sümbelli et al with a particular focus on the potential of using artificial cells within tissue engineering scaffolds for improved spatiotemporal control over cell-matrix interactions on the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In particular, human-based biomaterials can recapitulate the biochemical environment that cells feel in vivo and have been proposed, for example, as biocompatible hydrogel precursors. [8] Human-derived Platelet lysate (PL) offers great DOI: 10.1002/adfm.202214372 potential as a cocktail of growth factors, cytokines, and structural proteins. Studies have demonstrated remarkable features of PL in bone, tissue, and cartilage repair and localized wound healing.…”
Section: Introductionmentioning
confidence: 99%